3,4-Dihydroxybenzaldehyde thiosemicarbazone - Tan, Kong Wai; Ng, S.W.; Maah, Mohd Jamil; Ng, C.H.; Farina, Y. (International Union of Crystallography, 2008)
The asymmetric unit of the title compound, C8H9N3O2S, contains three independent molecules which are stacked approximately over each other. In the crystal structure, centrosymmetric pairs of molecules are formed through intermolecular hydroxy - hydroxy O - H center dot center dot center dot O and hydroxy sulfur O - H center dot center dot center dot S hydrogen bonds which are, in turn, linked into a two- dimensional network by N - H center dot center dot center dot O( hydroxy) hydrogen bonds.